Goodnight songs [compact disc] - Brown, Margaret Wise, 1910-1952; Proutt, Tom; Gary, Emily (Sterling Children's Books, 2014)
A previously unpublished collection of twelve lullabies, illustrated by contemporary, award-winning artists including Jonathan Bean, Sophie Blackall, Renata Liwska, and Dan Yaccarino.